Trying to Explain Home Bias in Equities and Consumption - Lewis, Karen K (Journal of Economic Literature, 1999)
Investors hold a substantially larger proportion of their wealth portfolios in domestic assets than standard portfolio theory would suggest, a phenomenon called “equity home bias.” In the absence of this bias, investors would optimally diversify domestic output risk using foreign equities. Therefore, consumption growth rates would tend to co-move across countries even when output growth rates do not. Empirically, however, consumption growth rates tend to have a lower correlation across countries than do output growth rates, a phenomenon I call “consumption home bias.” In this paper, I discuss these two biases and their potential relationship as suggested by the literature.